REKONSTRUKSI PENDIDIKAN KARAKTER DALAM RISĀLAH “ḤAYY BIN YAQẒĀN” KARYA IBN ṬUFAIL (Analisis Resepsi Sastra) - Latifi, Yulia Nasrul (Sunan Kalijaga State Islamic University Yogyakarta, 2018)
In the middle of seeking the concept of character education recently, risālah “Ḥayy bin Yaqẓān” offers an inclusive and holistic alternative in literature perspective. The risālah describes the life of the main character, Ḥayy, whose life is full of knowledge, wisdom, and values from chilhood to death. This research aims to show the reconstruction of character education pillars and the process of character education building. The material object of this research is a risālah entitled Ḥayy bin Yaqẓān written by Ibn Ṭufayl. The formal object is the reconstruction of character education. The theory applied here is a reception by Iser, using a content analysis method. The results of this analysis reveals that the risālah consist of reconstruction of education pillars reflected on the character of Ḥayy. They are a willingness to learn, proactive and has a positive contribution to his neigborhood, emphaty and compassionate, cognitive intelligence combined with a strength of soul, and be faithful in God. The reconstruction of the process of character education building is the internal factors (family), the external factors (millieu), and the principle of character education is a life long education.